2003
DOI: 10.1038/sj.bjc.6600982
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant mistletoe lectin induces p53-independent apoptosis in tumour cells and cooperates with ionising radiation

Abstract: Mistletoe extracts are used as alternative cancer treatment in addition to standard chemotherapy and radiation treatment and have an immunostimulatory and pain-relieving effect. A direct antitumour effect of mistletoe extracts against tumour cells of lymphoid origin has been linked to the D-galactoside-specific mistletoe lectin I. In this study, we investigated the cellular effect of bacterially expressed, recombinant mistletoe lectin alone or in combination with ionising radiation in a genetically defined p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 38 publications
1
34
0
2
Order By: Relevance
“…The CD75s-ganglioside specific viscumin and its recombinant counterpart rViscumin, both being under clinical investigation as potential antitumor drugs, are of particular interest due to their cancer-destructive potential. Besides their primordial antitumor activity on tumor cell lines including multidrug-resistant human cancer cell lines (38), synergistic antitumoral effects of the native and recombinant lectin have been documented in numerous in vitro studies employing conventional antitumor drugs (39) and ionizing radiation treatment (40). Furthermore, rViscumin has been successfully probed in treating cancer cells in animal models in vivo (41,42).…”
Section: Resultsmentioning
confidence: 99%
“…The CD75s-ganglioside specific viscumin and its recombinant counterpart rViscumin, both being under clinical investigation as potential antitumor drugs, are of particular interest due to their cancer-destructive potential. Besides their primordial antitumor activity on tumor cell lines including multidrug-resistant human cancer cell lines (38), synergistic antitumoral effects of the native and recombinant lectin have been documented in numerous in vitro studies employing conventional antitumor drugs (39) and ionizing radiation treatment (40). Furthermore, rViscumin has been successfully probed in treating cancer cells in animal models in vivo (41,42).…”
Section: Resultsmentioning
confidence: 99%
“…Aviscumine is a heterodimer, which is composed of a toxic A-chain, representing a site-specific type-II ribosome-inactivating N-glycosidase, and a carbohydrate-binding subunit B, responsible for its cellular uptake (7)(8)(9). The N-glycosidase-mediated catalytic inactivation of ribosomes leads to a time-and dose-dependent inhibition of protein translation and synthesis (GI 50 , 1 ng/ml) in various human tumor cell lines (10)(11)(12), independently of cell cycle or proliferation status (9,(12)(13)(14). As well as its direct cytotoxic effect, immunomodulatory activity of aviscumine was suggested in early clinical trials in which aviscumine demonstrated a clinical efficacy in various types of solid tumor with tolerable toxicity profiles (15)(16)(17)(18); this immunomodulatory effect was presumed based on increased levels of interleukin (IL) 1β, tumor necrosis factor a (TNF-α) and interferon g (IFN-γ) detected in patient sera during treatment (15).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16] Initiation of apoptosis is controlled by regulation of the balance a These authors equally contributed to this work. between life and death signals received by the cells.…”
Section: Introductionmentioning
confidence: 99%